2017
DOI: 10.1007/s00380-017-0977-4
|View full text |Cite
|
Sign up to set email alerts
|

Randomized comparison between provisional and routine kissing-balloon technique after main vessel crossover stenting for coronary bifurcation lesions

Abstract: We compared the myocardial ischemic burden of provisional and routine final kissing-balloon inflation (FKI) with the 1-stent strategy using a second-generation drug-eluting stent for coronary bifurcation lesions (CBL). There are no established guidelines for side branch (SB) intervention after main vessel stenting. In total, 113 CBL patients were randomized to receive different SB intervention strategies: provisional-FKI group (n = 57; FKI only when SB flow was TIMI <3) and routine-FKI group (n = 56; mandatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Clinical follow-up periods for the five trials ranged from 6 to 36 months. One trial reported outcomes beyond one year[ 12 ]. Angiographic follow-up and quantitative coronary angiography were performed 6–9 months after the index procedure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical follow-up periods for the five trials ranged from 6 to 36 months. One trial reported outcomes beyond one year[ 12 ]. Angiographic follow-up and quantitative coronary angiography were performed 6–9 months after the index procedure.…”
Section: Resultsmentioning
confidence: 99%
“…The rate of angiographic follow-up was 83%. Assessment of the treated vessels with intravascular ultrasound after stenting and at follow-up was performed in 3 of the studies [ 11 12 , 14 ]. Bifurcation lesions that included the left main stem were reported in 150 cases in 2 of the studies [ 10 , 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…The sum of the differences between these 2 scores de ned the summed difference score. The percent (%) myocardial ischemia (100 × summed difference score [SDS]/68) was calculated and a SDS ≥7 was considered to be ≥10% myocardial ischemia 5,11 .…”
Section: Study Design and Populationmentioning
confidence: 99%
“…One of its benefits is to optimize stent apposition, improve side branch entry and to correct stent deformation [6]. However, in complex anatomy, the procedure-time and contrast media are more increased than without kissing balloon [7,8]. KBI technique is the standard strategy in bifurcation lesions that are treated with the twostent technique, unfortunately, the benefit of this procedure in the one-stent approach remains uncertain due to poor clinical data [9].…”
Section: Introductionmentioning
confidence: 99%